2012
DOI: 10.1017/s0144686x12000566
|View full text |Cite
|
Sign up to set email alerts
|

Managing older workers during a period of tight labour supply

Abstract: This article reports on a recent survey of employer attitudes and policies towards older workers in Australia at a time of sustained economic growth and ongoing concerns about labour shortages. Findings from a survey of  employers with more than  employees in the State of Queensland point to an unusually strong orientation towards the recruitment of older workers among respondents, although the retraining of older workers is not prioritised by the majority. The issue of workforce ageing is viewed as being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…In Australia, some recent research findings support the notion that employers have a ‘strong orientation’ towards older workers as employees or potential employees (Taylor et al. ), while others have suggested that this group of workers remains marginalised and a lack of coherent policy direction is contributing to the problem (Kossen and Pedersen ).…”
Section: Influences On Retirementmentioning
confidence: 91%
See 1 more Smart Citation
“…In Australia, some recent research findings support the notion that employers have a ‘strong orientation’ towards older workers as employees or potential employees (Taylor et al. ), while others have suggested that this group of workers remains marginalised and a lack of coherent policy direction is contributing to the problem (Kossen and Pedersen ).…”
Section: Influences On Retirementmentioning
confidence: 91%
“…Evidence relating to the implementation of effective HRM policy in relation to older workers is somewhat mixed (Kramar ; Taylor et al. ). In addition, the GFC has complicated policy development; since the GFC worker supply has tended to exceed demand, and in these situations older workers are often targeted for redundancy rather than their younger colleagues (Encel and Ranzijn ).…”
Section: Influences On Retirementmentioning
confidence: 99%
“…; Taylor et al. ), but there is little evidence as to how, and to what extent, some prospective older employees act to counter these views and succeed against the tide in securing job opportunities. We need to explore what older job seekers themselves, and especially those who have been successful, believe to be the conditions that make them attractive to employers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research has mainly investigated environmental circumstances influencing employers’ hiring decisions about older people (Earl et al, 2015). As such, scholars have indicated that experienced difficulties in recruiting or labor shortages in general are likely to facilitate hiring older people (Taylor et al, 2013). On the other hand, high cost pressure is likely to lower older people’s hiring chances as that has been found to lower the probabilities for older workers to receive training and development (e.g., Erber and Danker, 1995; Loretto and White, 2006).…”
Section: Introductionmentioning
confidence: 99%